2022
DOI: 10.1108/jabs-11-2021-0475
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and marketing capabilities as determinants of firm performance: evidence from automotive industry

Abstract: Purpose This study aims to explore the roles and relations of dynamic capabilities (DCs) and marketing capabilities (MCs) to generate firm performance through new empirical data from the automotive industry in an emerging market, Turkey, where volatile market conditions may compel firms to use both their DCs and MCs. The automotive industry dynamic character, which is shaped by fierce competition among car manufacturers, fluctuating customer demands and strong effect of environmental forces, provides an ideal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 107 publications
1
32
0
2
Order By: Relevance
“…Our findings indicate that marketing capabilities have a significant direct impact on firm performance. These findings corroborate other studies (i.e., Cataltepe et al, 2022;Wilden & Gudergan, 2015) and once more highlight the importance of MCs of firms in sustaining competitive advantage. Pricing was the most influential MC on firm performance and marketing research, along with marketing strategy and implementation followed the pricing capability.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings indicate that marketing capabilities have a significant direct impact on firm performance. These findings corroborate other studies (i.e., Cataltepe et al, 2022;Wilden & Gudergan, 2015) and once more highlight the importance of MCs of firms in sustaining competitive advantage. Pricing was the most influential MC on firm performance and marketing research, along with marketing strategy and implementation followed the pricing capability.…”
Section: Resultssupporting
confidence: 91%
“…While product development refers to developing new products and services that offer new value to the customers, pricing is the capability of a price policy that leads the firm to gain maximum profit from the market (Morgan et al, 2018). Effective channel management decisions can create unique shopping experiences for customers, and marketing research helps firms collect adequate data about customer needs (Cataltepe et al, 2022). Marketing communication enables firms to maintain and maximize their personalized relations with customers, and marketing strategy and implementation-related decisions support firms in "selecting the most productive available resource combinations to match market conditions" (Kamasak, 2013, p. 243).…”
Section: Introductionmentioning
confidence: 99%
“…The mean number of years in business was 29.36, and the standard deviation was 23.31. Research (e.g., Cataltepe et al, 2022) revealed that firms which have been in business for longer periods of time and have been larger in size emitted a more favourable image to society. Additionally, Porter (1991, p. 98) argues that "industry occupies an inherently central role, either direct and/or indirect in determining the sustainability of strategic positioning and hence of performance.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, an emerging stream of research theorises that CPA and CSR can be combined, and the interactive effects of CPA and CSR can result in more positive organisational outcomes since CPA and CSR complement each other. CPA and CSR are both relational constructs, and they include many "relational activities such as media campaigns, lobbying, philanthropy, and interactions with NGOs, government and bureaucrats" (De Roeck et al, 2016;Hillman et al, 2004) which can influence stakeholder evaluations of firms' actions and create favourable or unfavourable perceptions of image and prestige that endow firms with competitive advantages (Cataltepe et al, 2022;den Hond et al, 2014;Kamasak, 2017;Kamasak et al, 2019b;Morsing & Roepstorff, 2015;Rindova et al, 2010).…”
Section: Cpa Csr and Corporate Reputationmentioning
confidence: 99%
“…Given this void, Cataltepe et al (2022) consider the issues in a study of companies operating within Turkey’s automotive industry, the fourth-largest in Europe. It is the nation’s biggest export industry and is closely associated with other sectors like petroleum, chemicals and metals.…”
Section: Evidence From Turkeymentioning
confidence: 99%